Tratamiento neuro dinámico en neuropatía periférica en pacientes diabéticos. - Rosero Romero, Jefferson Alexander (2024)
The research corresponds to a bibliographic compilation of articles annexed to scientific databases such as PubMed, Scopus, Science Direct, Scielo, and Dialnet with the objective of identifying the effects of neurodynamic treatment on peripheral neuropathy in diabetic patients; the analyzed and selected studies met rigorously with the inclusion and exclusion criteria. The methodology applied was a documentary type, with an inductive method, descriptive level and design, qualitative approach, and retrospective in nature. Diabetic peripheral neuropathy is a neurodegenerative disorder of hyperglycemia that is stored in the peripheral nerve, affecting sensory, autonomic, and, to a lesser extent, motor axons, causing pain, burning sensations, numbness, extreme sensitivity, and tingling. Neural mobilization helps a lot in patients with anomalies in the nervous system, musculoskeletal disorders, and comorbidities. At the end of the analysis and interpretation of the scientific articles, it is stated that sliding and tensioning neurodynamic techniques are effective in the diagnosis, evaluation, and treatment of patients with diabetic peripheral neuropathy, reducing pain, improving ranges of movement and neural mechanosensitivity, increases nerve conduction speed, improving the quality of life of patients. Neurodynamics added to other treatments brings better results.